Questions Analysis in Mathematics Textbook from Competency-Based Curriculum up to Curriculum 2013 - Raditya, Aji; Iskandar, Ratu Sarah Fauziah; Suwarno, Suwarno (Desimal: Jurnal Matematika, 2020)
Mathematics textbooks have a significant role in mathematics teaching, and learning activities in schools and the questions contained in textbooks are usually used by students to practice independently. The purpose of this study is to analyze the types of problems in mathematics textbooks used from 2000 to 2017 in Indonesia, especially in the material of one-variable linear equations. The method used in this study is a six-dimensional analysis method, which consists of mathematical activities, the level of difficulty of the questions, the types of answers expected, contextual situations, the types of responses and the types of mathematical questions. Data collection techniques are done by analyzing and describing the types of questions in mathematics textbooks used from 2000 to 2017. The results of this study are the problems in mathematics textbooks for linear variable equations of one variable that do not have diverse types, the types of questions in textbooks are still many in the form of questions that calculate or use a variety of arithmetic operations, apply directly the basic knowledge or skills and without context in everyday life. Also, the existing questions are questions with closed answers, namely questions that only require answers without a reason and questions with a single procedure